2003
DOI: 10.3148/64.4.2003.202
|View full text |Cite
|
Sign up to set email alerts
|

Eat Smart! Ontario's Healthy Restaurant Program: A Survey of Participating Restaurant Operators

Abstract: Eat Smart! Ontario's Healthy Restaurant Program is a standard provincial health promotion program. Public health units grant an award of excellence to restaurants that meet designated standards in nutrition, food safety, and non-smoking seating. The purpose of this study was to assess whether program objectives for participating restaurant operators were achieved during the first year of program implementation, and to obtain operators' recommendations for improving the program. Dillman's tailored design method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…The context for studies varied greatly, with 15 Organization for Economic Co‐operation and Development (OECD) countries represented. The majority of studies were conducted in the United States (n = 56) or Canada (n = 13) . Studies encompassed food service (n = 44), grocery (n = 56), and mixed (n = 7) retail settings including cafeterias (n = 24), full service restaurants (n = 18), corner stores and/or grocery stores (n = 19), supermarkets (n = 16), vending machines (n = 13), quick‐service restaurants (n = 13), and cafés (n = 5)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The context for studies varied greatly, with 15 Organization for Economic Co‐operation and Development (OECD) countries represented. The majority of studies were conducted in the United States (n = 56) or Canada (n = 13) . Studies encompassed food service (n = 44), grocery (n = 56), and mixed (n = 7) retail settings including cafeterias (n = 24), full service restaurants (n = 18), corner stores and/or grocery stores (n = 19), supermarkets (n = 16), vending machines (n = 13), quick‐service restaurants (n = 13), and cafés (n = 5)…”
Section: Resultsmentioning
confidence: 99%
“…Six initiatives were retailer‐led, 29 were the result of partnerships, and 41 were researcher‐led, with the remainder government‐, industry‐, or health organization‐led. More than half of the included studies (n = 66) identified one or more business outcomes in the primary aim of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, point-of-purchase interventions that use cues such as signage with nutrient information or price manipulation tend to show an increase in the purchase of healthier options (Buttriss et al, 2004; French, Jeffery, Story, Hannan, & Snyder, 1997; Holdsworth & Haslam, 1998; Horgen & Brownell, 2002). In addition, some research shows that most restaurant owners want their restaurant to be viewed as a place where customers can find healthy options (Benson, 1995; Macaskill, Dwyer, Uetrecht, & Dombrow, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that many restaurant owners want their restaurant to be seen as providing healthy options (Benson, 1995; Macaskill, Dwyer, Uetrecht, & Dombrow, 2003). Research also suggests that programs that promote simple changes to the usual menu offerings may be more acceptable to restaurant owners than those that require posting of nutritional information (Green, Steer, Maluk, Mahaffey, & Muhajarine, 1993).…”
Section: Introductionmentioning
confidence: 99%